Computation of heat transfer in magnetised Blasius flow of nano-fluids with suspended carbon nanotubes through a moving flat plate. Issue 1 (31st December 2022) - Ferdows, M.; Shamshuddin, MD.; Salawu, S. O.; Reza, Motahar
Abstract : This paper examines a two-dimensional steady, incompressible and laminar hydro-magnetic flow along with the transfer of heat above a plane plate that contains water and ethylene glycol-based nano-fluids with multi- and single-wall CNTs. The plate surface is subjected to variable wall temperatures. The transfer of heat has been contemplated in suspended CNTs above a plane plate. Navier–Stokes and the concept of the Prandtl boundary layer have been used to determine the governing equations of heat transfer and flow. Since the attained governing equations representing energy and flow are non-linear PDEs, they are altered into non-linear ODEs accompanied by analogous boundary conditions by applying several appropriate similarity transformations. Hence, the 'bvp4c ' function is used to solve them numerically. Various graphs with physical interpretation demonstrate the consequence of determining terms on the characteristics of the flow. The plate velocity parameter and volume fraction have a positive effect. Temperatures are elevated markedly for most of the governing parameters. The rate of heat transfer and temperature exponent are enhanced by a magnetic field. SWCNTs give more substantial heat transfer than MWCNTs.